Preparation and characterisation of hyperbranched poly divinyl benzene and star branched poly lactic acid blends and their composites - Kabir, Sumaya Farhana (2017)
This thesis explored the use of hyperbranched poly divinyl benzene and star shaped polylactic acid polymers as blend constituents with their respective linear analogues and also explored the use of those blends as matrices for E glass fibre composites. Investigations into their effects on the composite mechanical properties were conducted. Hyperbranched poly divinyl benzene (HB2) with reactive (-vinyl; -CH=CH2) and hydrogenated hyperbranched polyl divinyl benzene (H-HB2) with non-reactive (ethyl; -CH2-CH3) functional groups were used in this study as blend constituents with linear polystyrene (LP), since HB2 materials were too brittle to produce films. HB2 with reactive functional groups were crosslinked at high temperature which increased the glass transition temperature (Tg), thermal stability, viscosity and the tensile modulus (only after heat treatment at 200C) of HB2 blends (LP-HB2) in comparison to LP. On the other hand, for blends with H-HB2 (LP-H-HB2), lower Tg, higher thermal stability, lower viscosity and lower tensile modulus (even after heat treatment at 200C) was observed in comparison to LP. However, for heat treated LP-H-HB2 80-20 (containing 20wt% of H-HB2 in blend with LP) chain end crystallisation was observed which significantly (p<0.05) increased the tensile modulus and strength of the blend in comparison to its value at room temperature. From the rheological studies LP-HB2 blend was suggested to have been crosslinked across the whole temperature region, whereas LP-H-HB2 blend showed flow behaviour at lower temperature (~175C) in comparison to LP (~190C). Composites were then prepared using LP-HB2 and LP-H-HB2 blends as matrices and E-glass fibre as reinforcement. No significant (p<0.05) improvement was observed for the composites using LP-HB2 blend due to the poor wettability of crosslinked LP-HB2 with fibre. However, a significant (p<0.05) improvement in flexural modulus and strength for composites prepared using LP-H-HB2 80-20 as matrix was observed in comparison to composites prepared using LP as matrix. Six arm star PLA (SPLA) of four different mol. wt. (3,6,9 and 12 kDa) was used in this study as blend constituents with linear PLA and the blends were also used as matrices for composites manufacture with E-glass fibre as reinforcement. Blending SPLA with linear PLA decreased the Tg, Tm and Tc properties, thermal stability, % crystallinity and viscosity of the blends both at room temperature and also after heat treatment (at 175C), however, increase in their hydrolytic degradation rate was observed. These blends when used as matrices for composites revealed significantly increased flexural moduli and strength profiles in comparison to linear PLA, which was attributed to the better wettability of the blend matrices due to their lower viscosity and crystallinity. The highest flexural modulus and strength profiles (which increased by 57% and 77% respectively) were found for composite samples prepared using blends of linear PLA with highest mol. wt. (Mn) SPLA (PLA-12 80-20-GF) in comparison to the composite with linear PLA as matrix. Moreover, increased hydrolytic degradation rate was observed for SPLA blended composites due to their lower crystallinity and also due to the presence of hydroxyl (-OH) groups at the chain ends of SPLA which promoted hydrolytic degradation rates.